Amnesty: Title IX Policies and Christian Colleges. Issue 3 (26th May 2020) - Graber, Britney N.
Abstract: Underreporting of sexual assault on college campuses is a growing concern for institutions of higher education. Amnesty clauses in Title IX policies intend to reduce barriers to reporting, encouraging victims and witnesses to come forward with any knowledge or experience of an incident of sexual assault. However, little research has been conducted on Christian college campuses and Title IX issues. In an effort to close this scholarly gap, this study explores the 112 Council for Christian Colleges & Universities (CCCU) member institutions located in the United States to determine what, if any, types and extent of amnesty they afford complainants and/or witnesses during Title IX investigations. The findings of this study demonstrate that some form of amnesty provision is apparent in about half of CCCU institutions. However, after a content analysis of these institutions' Title IX policies, this study reveals that only five out of the 112 CCCU member institutions afford complete and comprehensive amnesty to complainants and witnesses during a Title IX investigation. As relevant literature and federal Title IX guidance suggest, this lack of true amnesty has major implications for Title IX reporting and best practices on Christian college campuses.